The Influence of Return On Assets (ROA), Return On Equity (ROE), Net Profit Margin (NPM), on Stock Prices (Case Study of Coal Sub-Sector Mining Companies Listed on the Indonesia Stock Exchange - Abu Darim; Naning Tri Rahayu (Sekolah tinggi ilmu ekonomi pemuda, 2022)
Fundamental analysis is an approach that is often used in predict stock prices movement, The issue raised in this study is how the influence of the ROA, ROE, and NPM against stock prices of mining companies coal sub sector listed on the stock exchange in 2018-2019. The Population in this study were mining companies coal sub sector listes on the stock exchange in 2018-2019 a many 32 company. Sample in this research 21 company and using proporsionate random sampling and data collection in this research using secondary data were data quantitative which calculate using ratio analysis. Analysis Result on this study showing return on assets (ROA) has positif significantly on stock prices with coefficient 0.929 or 9,29%. Based on the calculate t-table showing that Return of Equity (ROE) Positif not Significantly result on stock stock prices with coefficient 0.054 or 5,4% as well as from the result of this study showing that Net Profir Margin (NPM) has Positive Significantly on stock prices with Coefficient -,0.306 or 30,6%.